The Effectiveness of Integrated Management Packages in Controlling Aphid-Borne Virus Infections on Groundnut in South Sulawesi, Indonesia - Kasim, Niken Nur; Damayanti, Tri Asmira; Hidayat, Sri Hendrastuti; Santoso, Sugeng (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2024)
Aphid-borne viral infection is a major limiting factor for groundnut production in South Sulawesi, Indonesia. The study aimed to elucidate the effectiveness of integrated management packages (IMP) in controlling aphid-borne viruses infecting groundnut in the field. Field trials were conducted in a plot without (M0) and with plastic mulch and maize as a plant barrier (M1), while two different groundnut varieties, Bougainvillea leaf extract, and insecticides were incorporated as the subplot treatments. The treatments in M1 plot significantly reduced the aphid population (17.4–79.9%) and AUDPC incidence (51.7–87.3%), and severity (61.0–92.9%), respectively. The treatments increased dry pod production by 11.9–63.3% depending on subplot treatment compared to treatments in the M0 plot (p>0.05). Bean common mosaic virus strain PSt and Cowpea Polerovirus 2 were positively detected in groundnuts as well as in aphids using RT-PCR. Further, nine weed species in the vicinity of the field trial were found to be positively infected with BCMV-PSt, indicating their crucial role as reservoir hosts. Interestingly, the effectiveness of Bougainvillea leaf extract treatment in the M1 plot was comparable to that of the insecticide treatment, indicating that this IMP is a more cost-effective, eco-friendly groundnut virus control than the currently used method.